Decision/therapeutic algorithm for acetabular revisions - Aprato, Alessandro; Olivero, Matteo; Di Benedetto, Paolo; Massè, Alessandro (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: Paprosky’s classification is currently the most used classification for periacetabular bone defects but its validity and reliability are widely discussed in literature. Aim of this study was to introduce a new CT-based Acetabular Revision Algorithm (CT-ARA) and to evaluate its validity. The CT-ARA is based on the integrity of five anatomical structures that support the acetabulum. Classification’s groups are defined by the deficiency of one or more of these structures, treatment is based on those groups. Methods: In 105 patients the validity of the CT-ARA was retrospectively evaluated using preoperative X-rays, CT-scan and surgery reports. The surgical indications suggested by Paprosky’s algorithm and by CT-ARA were compared with the final surgical technique. Patients were divided into two groups according to time of surgery. Results: We reported concordance of indications in 56,2% of cases with the Paprosky’s algorithm and in 63,8% of cases with the CT-ARA. Analysing only the most recent surgeries (group 2), we reported even higher difference of concordance (67,3% Paprosky’s algorithm and 83,7% CT-ARA). The concordance of the CT-ARA among Group 1 and Group 2 resulted significantly different. Conclusions: the CT-ARA may be a useful tool for the preoperative decision-making process and showed more correlation with performed surgery compared to the Paprosky’s algorithm.